Anti‐IgLON5 Disease with Isolated Hemichorea: A Case Report and Review of the Literature. Issue 1 (24th November 2022) - Grossauer, Anna; Hussl, Anna; Mahlknecht, Philipp; Peball, Marina; Heidbreder, Anna; Deisenhammer, Florian; Djamshidian, Atbin; Seppi, Klaus; Heim, Beatrice
Abstract: Background: Anti‐IgLON5 disease is an autoimmune encephalopathy with sleep disturbances as a hallmark in the majority of reported cases. Additional clinical symptoms are heterogenous and include movement disorders, bulbar dysfunction, autonomic disorders, and neurocognitive impairment. Case: Here, we report the case of an 87‐year‐old woman presenting with isolated progressive hemichorea. An extensive diagnostic work‐up revealed antibodies against IgLON5 in the serum. Neither history nor polysomnography (PSG) unveiled signs and features of sleep dysfunction typically reported in anti‐IgLON5 disease. Literature Review: In an extensive literature review we identified twelve other studies reporting about patients with confirmed anti‐IgLON5 disease and chorea as extrapyramidal movement disorder in their clinical phenotype. Subsequently, clinical characteristics of these patients were carefully evaluated. Conclusions: Our results support the diversity of clinical phenotypes in anti‐IgLON5 disease, adding isolated hemichorea to the spectrum of presenting symptoms. As sleep‐related disorders are often not the leading reason for consultation and only revealed by PSG examination, we suggest that screening for antibodies against IgLON5 should be considered in patients presenting with unexplained movement disorders, including isolated hemichorea.